Predictors of maternal recidivism in the child protection system - Ahn, Eunhye (Child maltreatment, 2023)
Child maltreatment recidivism is typically measured and studied at the individual level. Conditions that give rise to child abuse and neglect, however, typically affect multiple children in a given family. In the current study, we estimated maltreatment recidivism at the maternal level and examined its risk as a function of maternal sociodemographic characteristics that may change over time. Using linked administrative records, we identified a subset of first-time mothers in California whose first child was reported to the child protection system (CPS) between birth and age 5 and who then gave birth to another child (n = 14,715). Following the firstborn child's CPS reporting, nearly half of these mothers (43.3%) were re-reported concerning the non-firstborn children during the first 5 years of the child's life. Risk factors consistently documented across births were associated with a heightened risk of maternal CPS recidivism. Our study advances an understanding of the full extent of maltreatment recidivism by broadening the focus from individual children.